Soybean-derived phospholipids complexed poly (lactic-co-glycolic acid) nanofibrous scaffolds for tissue engineering applications. (July 2021) - Mao, Ying; Guidoin, Robert; Li, Yan; Brochu, Gaetan; Zhang, Ze; Wang, Lu
Graphical abstract: Highlights: Novel phospholipids complexed nanofibrous scaffolds were readily fabricated. The resulted scaffolds showed favorable morphology and tunable wettability. The degradation behavior was notably accelerated by incorporating phospholipids. The phospholipids complexed scaffolds exhibited improved biocompatibility. Abstract: Polymeric scaffolds play a vital role in tissue engineering. Electrospun poly (lactic-co-glycolic acid) (PLGA) membranes can be a promising scaffold. However, their applications are restricted due to poor hydrophilicity and single function. In this study, we show for the first time how blending of L-α-phosphatidylcholine (PC) to PLGA to yield hybrid scaffolds alters the physical properties and wettability and consequently affects the biodegradability and biocompatibility. Soybean-derived phospholipids complexed PLGA nanofibrous scaffolds (PLGA-PC) were readily fabricated by electrospinning polymer solutions of PLGA and PC in different ratios. The obtained scaffolds exhibited a dramatic decrease in fibre diameter and a significant increase in porosity and hydrophilicity as the PC component was added. Although the mechanical strength of PLGA scaffolds decreased due to the incorporation of PC, the PLGA-PC groups showed tensile strength above 2.5 MPa in both dry and wet states. Based on in vitro degradation, we found that it was accelerating for PLGA-PC scaffolds with PC content increased. Additionally, these scaffolds presented superior blood compatibility and cytocompatibility. The explored research on phospholipids complexed scaffolds can readily extend to other polymers and provides a feasible strategy to construct optimal microenvironments for seeded cells, indicating promising use in various tissue engineering.